Rights to protection and the state: the Australian Government’s National Plan to reduce violence against women and children and victim’s justice - Guthrie, Rob (Taylor and Francis, 2018)
Due to increased awareness and impact of domestic violence, women's safety in the domestic sphere has become a prominent problem in Australian politics. In an analysis of criminal injuries compensation (CIC) processes in WA, this paper highlights a specific aspect of national policy failure in relation to safety for women who have experienced domestic and family violence. It establishes policy impetus to acknowledge a right to protection by the state within the domestic sphere, then discusses the history and relevance of state responsibility/obligations for victims of crime compensation and demonstrates how the failure to comply with the nationally endorsed plan to address domestic violence places some women at risk of further harm. The example of WA's victims of crime compensation processes highlights the high level of female domestic violence victims using the scheme and important intersectional issues pertinent for Indigenous women. The paper points to how a specific failure of policy implementation may be addressed.